Interpreting The Stress of Work - Bhana, Arvin; Pillay, Yogan (PINS-Psychology in Society, 2026)
The study of the psychosocial work environment has burgeoned over the last two decades, much of which has been concerned with the detrimental effect of the workplace on physical and mental health. It has also been recognized as one of the most important sites of social and psychological well-being (Johnson & Johansson, 1991). The use of interpretative methods in understanding the complex relationships between worker and work settings has seldom been employed, either as a research strategy, or as way of developing a participatory agenda between researcher and subject. This paper reflects the use of an interpretative methodology in understanding the work environment of union organizers and its place in developing a model for participatory research.